2016
DOI: 10.30897/ijegeo.306484
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Vulnerability Analyses for Functional Zoning in a Coastal District of Turkey

Abstract: Functional zoning of Akcakoca District located along the Western Black Sea Coast of Turkey is achieved by implementing the 'Methodology for Spatial Planning for the Coastal Zone' developed by European Union for coastal areas. The aim of applying the methodology was to realize functional zoning of the district that will eventually lead to spatial planning. In this technique, a typical base map at an appropriate scale and thematic layers are prepared for each of the environmental components for further analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this method, a typical basemap is made at appropriate scale, and overlay maps are generated for each of the components or attributes of the environment to be further analyzed. The possibility of different layers overlapping in accordance with required procedure and implementation of new thematic view is important factor in functional zoning [34]. Zoning is an operational mechanism by which current and projected land use is spatially defined in the form of zoning map identifying areas where different land uses are permitted [4].…”
Section: Methodsmentioning
confidence: 99%
“…In this method, a typical basemap is made at appropriate scale, and overlay maps are generated for each of the components or attributes of the environment to be further analyzed. The possibility of different layers overlapping in accordance with required procedure and implementation of new thematic view is important factor in functional zoning [34]. Zoning is an operational mechanism by which current and projected land use is spatially defined in the form of zoning map identifying areas where different land uses are permitted [4].…”
Section: Methodsmentioning
confidence: 99%
“…These qualities change temporally and spatially. Education level, gender, age, dominant economic activity, disaster knowledge, religion and culture, state of health, income, land use methods and knowledge of hazards, ethnicity, and the ability to benefit from technological opportunities are among those quality items that could determine the capacity to which the population would be able to assess and cope with a flood efficiently, and is of great importance (Etkin, 1999;Ferrier & Haque, 2003;Şeker et al, 2016;Gazioğlu, 2018). Sattler et al (2000) studied the relationship of natural disaster preparedness with age, and found that age had a positive linkage with disaster prevention preliminaries.…”
Section: Introductionmentioning
confidence: 99%
“…They are also main source for oxygen in sea water with their ability to mass photosynthesis at marine ecosystems. Posidonia oceanica (L.) presence, dimensions, health status, distribution is an important ecological-bioindicators indicator, and gives an illuminating profile about the general situation of the environment is emphasized in various publications (Gazioğlu, 2018;Şeker et al, 2016;Simav et al, 2015;Boudouresque et al, 2012;Royo et al, 2011). As it's known, there are approximately 60 species of seagrass meadows which creates important ecological habitats in shallow water or tropical coastal areas of worldwide (Abadie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%